2021
DOI: 10.1016/j.ajog.2020.08.103
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for a placental microbiome in human pregnancies at term

Abstract: BACKGROUND: The placenta plays an important role in the modulation of pregnancy immunity; however, there is no consensus regarding the existence of a placental microbiome in healthy full-term pregnancies. OBJECTIVE: This study aimed to investigate the existence and origin of a placental microbiome. STUDY DESIGN: A cross-sectional study comparing samples (3 layers of placental tissue, amniotic fluid, vernix caseosa, and saliva, vaginal, and rectal samples) from 2 groups of full-term births: 50 women not in labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 70 publications
6
66
0
Order By: Relevance
“…Traditionally, the placenta is considered a sterile organ 107,108 . Indeed, recent research has reiterated the sterile womb hypothesis using placentas from women who delivered via cesarean section at term without labor [109][110][111] as well as studies in mice 112,113 and non-human primates 114 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, the placenta is considered a sterile organ 107,108 . Indeed, recent research has reiterated the sterile womb hypothesis using placentas from women who delivered via cesarean section at term without labor [109][110][111] as well as studies in mice 112,113 and non-human primates 114 .…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the placenta is considered a sterile organ 107 , 108 . Indeed, recent research has reiterated the sterile womb hypothesis using placentas from women who delivered via cesarean section at term without labor 109 111 as well as studies in mice 112 , 113 and non-human primates 114 . Here, we evaluated the possibility that maternal SARS-CoV-2 infection compromises the sterility of the placenta by facilitating the invasion of bacteria or the transfer of bacterial DNA from maternal compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, studies using 16S rRNA gene amplicon sequencing support the idea that the noise is too high to draw consistent conclusions about a ‘microbiome’ in the villous placenta. Research supporting the sterile womb hypothesis posits that data suggesting the presence of microbial communities in the placenta are actually due to contamination of placental samples during delivery or during the processing of bacterial DNA [ 15 , 16 ]. For example, using 16S rRNA sequencing, De Goffau and colleagues identified several sources of contamination, including labor and delivery and sample processing that are associated with different bacterial signals and concluded that they find no clear evidence of a placental microbiome.…”
Section: Group Therapy: Let Us Talk About the Differencesmentioning
confidence: 99%
“…They identified some samples with low biomass bacterial signal, but concluded that the source of this signal was due to contamination. Similarly, Sterpu et al found no significant differences between placental samples and controls based on 16S data, with the majority of their samples being flagged as contaminants by decontamination software [ 16 ]. However, they found that the median gene counts for bacterial signal were highest for the maternal side of the placenta regardless of the mode of delivery and indeed detected sporadic bacteria.…”
Section: Group Therapy: Let Us Talk About the Differencesmentioning
confidence: 99%
“…If a unique microbiome existed in the placenta an immunologically naïve foetus could be overwhelmed [ 51 ]. Therefore, there may be bacteria present at a low level in the placenta but given the function of the placenta, normal bacterial colonisation and development of a placental niche seems unlikely [ 59 ].…”
Section: Placental Microbiotamentioning
confidence: 99%